"Decoding hereditary breast cancer" benefits and questions from multigene panel testing. (June 2019) - Colas, Chrystelle; Golmard, Lisa; de Pauw, Antoine; Caputo, Sandrine M.; Stoppa-Lyonnet, Dominique
Abstract: Multigene panel testing for breast and ovarian cancer predisposition diagnosis is a useful tool as it makes possible to sequence a considerable number of genes in a large number of individuals. More than 200 different multigene panels in which the two major BRCA1 and BRCA2 breast cancer predisposing genes are included are proposed by public or commercial laboratories. We review the clinical validity and clinical utility of the 26 genes most oftenly included in these panels. Because clinical validity and utility are not established for all genes and due to the heterogeneity of tumour risk levels, there is a substantial difficulty in the routine use of multigene panels if management guidelines and recommendations for testing relatives are not previously defined for each gene. Besides, the classification of variant of unknown significance (VUS) is a particular limitation and challenge. Efforts to classify VUSs and also to identify factors that modify cancer risks are now needed to produce personalised risk estimates. The complexity of information, the capacity to come back to patients when VUS are re-classified as pathogenic, and the expected large increase in the number of individuals to be tested especially when the aim of multigene panel testing is not only prevention but also treatment are challenging both for physicians and patients. Quality of tests, interpretation of results, information and accompaniment of patients must be at the heart of the guidelines of multigene panel testing. Highlights: Multigene panel allows to sequence a high number of genes in numerous individuals. Management and relative testing guidelines need to be defined for each gene. Variant classification is a challenge amplified by NGS. Quality of tests, information and accompaniment of patients are testing guidelines. Tumour DNA is the native DNA of the patient!.